Gender differences in response to Facebook status updates from same and opposite gender friends. (May 2016) - Joiner, Richard; Cuprinskaite, Juste; Dapkeviciute, Lina; Johnson, Helen; Gavin, Jeff; Brosnan, Mark
Abstract: We conducted two studies to examine gender differences in response to Facebook status updates from same and opposite gender friends. Study 1 surveyed 522 undergraduate students (216 females and 306 males), and compared males' and females' responses to two Facebook status updates: one from a same gender friend and one from an opposite gender friend. Females' public replies and private messages to a female friend showed higher levels of emotional support than males' public replies and private messages to a male friend. In contrast, there were no significant gender differences in response to an opposite gender friend. Furthermore, males showed higher levels of emotional support in private messages than in public replies to male friends. Study 2 recruited 484 participants (295 females and 189 males) using CrowdFlower. Approximately half received a Facebook status update from a same gender friend and the other half received it from an opposite gender friend. Females' public replies to a female friend showed significantly high levels of emotional support than males' public replies to a male friend and there was a similar but marginally significant gender difference for private replies to same gender friends. There was no gender difference in response to opposite gender friends. The practical and theoretical implications of these findings are discussed. Highlights: Studies on gender differences to Facebook status updates from male or female friends. Females' levels of emotional support was higher than males to same gender friends. Males' levels of emotional support in private was higher than in public to male friends. There was no gender difference in response to opposite gender friends.